The architecture of food safety control in the European Union and the Eurasian Economic Union - David Sedik; Carl Ulbricht; Nuritdin Dzhamankulov (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2016)
The system of surveillance and control of food safety and animal and plant health is a vital building block of the single market in both the European Union (EU) and the Eurasian Economic Union (EAEU). The free movement of goods (the first of the four fundamental freedoms of the EU and the EAEU) throughout the union depends on the proper functioning of a union-wide system of assessment and control of food safety and animal and plant health risks. Sanitary and phytosanitary measures taken in response to a food safety threat, while they are a necessary part of the system for food safety control, are barriers to the free movement of goods within the union. They can be avoided only by ensuring an effective system of preventative control. While food safety is a worthwhile goal in and of itself, it is important to recognize that it is also an indispensable "pillar" upon which the free movement of goods rests. [...] The present analysis of the "architecture" of food safety control systems in the European Union and the Eurasian Economic Union is designed to assess the degree to which the present systems in the two unions can ensure effective food safety control, thus ensuring the free movement of goods within the single market. It is a comparative analysis of the EU and EAEU systems for ensuring food safety through sanitary and phytosanitary measures (Box 1). The analysis spans both central and country level institutions for ensuring food safety in the countries of these two economic unions. We first compare laws, institutions and the governance of food safety issues in the two unions at the supranational level. Second, we describe and compare the food safety systems at the country level in both unions. Last, we provide a synthetic conclusion that reports our findings about the key differences between food safety control in the European Union and the Eurasian Economic Union. We conclude that there are cardinal differences between the food safety systems in the two unions both at the central and country levels. The overhaul of the EU food safety control system in the 2000s led to a significant transfer of decision making authority to EU institutions. Very little, if any, of the EU-type central edifice exists in the Eurasian Economic Union. In fact, despite the existence of the Eurasian Economic Commission, the Eurasian Economic Union operates an extremely decentralized system of food safety control. At the country level the roles and responsibilities of institutions, while relatively clear in the EU countries, are not well defined or well understood in the countries of the EAEU. There are also major differences in the accession process within the two unions. While in the EU this is a long and transformative process, it is more a political process in the EAEU. Finally, while the EU seems to have a relatively effective system of food safety control, we find that in the EU the lack of Union-wide rules concerning the system of national controls means that there is no guarantee of coherence or comprehensiveness.
urn:nbn:de:gbv:3:2-59237
Keywords: 330